2020
DOI: 10.3389/fimmu.2020.566781
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and IFN-β Modulate the Inflammatory Gene Expression Program of Primary Human T Lymphocytes

Abstract: IFN-β treatment is a commonly used therapy for relapsing-remitting multiple sclerosis (MS), while vitamin D deficiency correlates with an increased risk of MS and/or its activity. MS is a demyelinating chronic inflammatory disease of the central nervous system, in which activated T lymphocytes play a major role, and may represent direct targets of IFN-β and vitamin D activities. However, the underlying mechanism of action of vitamin D and IFN-β, alone or in combination, remains incompletely understood, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The intronic variant rs2254210, associated in our analysis with Irf8 plasma levels, is located on the VDR gene and encodes for the vitamin D receptor (Vdr), a transcription factor that binds and regulates different genes [ 78 ]. Since the IRF8 locus has been shown to be directly bound by Vdr [ 78 , 79 ], the association found between rs2254210 and Irf8 plasma levels in our analysis further highlighted the functional link between the two proteins involved in autoimmune disease risk [ 78 , 80 ]. Regarding SNPs associated with Ptger4 plasma levels in our analysis, intronic variants rs17044638, located on the SATB1 gene, and rs3791268, located on the MGAT5 gene, resulted each associated with respective gene expression [ 81 ]; Ptger4 biological function is correlated with both SATB1 and MGAT5 protein products, i.e., Satb1 and Mgat5, as all these proteins have been linked to MS risk due to the role played in T cell differentiation, proliferation, and activation [ 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Discussionsupporting
confidence: 57%
“…The intronic variant rs2254210, associated in our analysis with Irf8 plasma levels, is located on the VDR gene and encodes for the vitamin D receptor (Vdr), a transcription factor that binds and regulates different genes [ 78 ]. Since the IRF8 locus has been shown to be directly bound by Vdr [ 78 , 79 ], the association found between rs2254210 and Irf8 plasma levels in our analysis further highlighted the functional link between the two proteins involved in autoimmune disease risk [ 78 , 80 ]. Regarding SNPs associated with Ptger4 plasma levels in our analysis, intronic variants rs17044638, located on the SATB1 gene, and rs3791268, located on the MGAT5 gene, resulted each associated with respective gene expression [ 81 ]; Ptger4 biological function is correlated with both SATB1 and MGAT5 protein products, i.e., Satb1 and Mgat5, as all these proteins have been linked to MS risk due to the role played in T cell differentiation, proliferation, and activation [ 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Discussionsupporting
confidence: 57%
“…Numerous previous studies have reported the modulation of CD4 T cell differentiation by 1,25(OH) 2 D 3 , but only one previous study has focused on γδ T cells [28]. The accumulated evidence supports the notion that vitamin D 3 inhibits CD4 T cell proliferation and inhibits their inflammatory gene program by suppressing IL-17 and IL-9 and favoring IL-10 induction [19,[72][73][74][75]. A recent molecular analysis demonstrated that Th1 cells could turn off their proinflammatory cytokine program in an autocrine manner and switch to IL-10 production in response to vitamin D 3 , a process that depends on several transcription factors, including c-JUN, STAT3, and BACH2 [23].…”
Section: Discussionmentioning
confidence: 89%
“…Hsa-miR-146b-5p had a significant protective effect on childhood asthma in the vitamin D insufficient group and the significant risk effect in the vitamin D sufficient group. Bianchi and colleagues validated that hsa-miR-146b-5p was upregulated in T cells when treated with vitamin D [32]. Hsa-miR-146b-5p shared the same "seed" in sequence with hsa-miR-146a-5p which exhibited strong anti-inflammatory effect by down-regulating the expression of NF-κB [33,34].…”
Section: Discussionmentioning
confidence: 97%